Enhancement of thermoelectric efficiency of CoSb3-based skutterudites by double filling with K and Tl - Kurosaki, Ken; Li, Guanghe; Ohishi, Yuji; Muta, Hiroaki; Yamanaka, Shinsuke (Frontiers in Chemistry, 2014)
The high-temperature thermoelectric properties of thallium (Tl) and potassium (K) double-filled cobalt antimonide (CoSb3)-based skutterudites with nominal compositions TlxK0.3Co4Sb12 (x = 0.1–0.3) were investigated. The filling fraction of Tl in CoSb3 was enhanced by co-filling with K, which resulted in all of the samples showing the filled-skutterudite single phase. Owing to the high filling ratio, the carrier concentration in the sample with x = 0.3 was as high as 4.3 × 1020 cm−3 at room temperature. Furthermore, quite low lattice thermal conductivity (as low as 0.9 W m−1 K−1) was obtained for the sample with x = 0.3, probably because of strong phonon scattering by the Tl and K co-rattling effect, which resulted in a maximum zT of around one at 773 K.